Misgav Ladach versus Kerr cesarean section: Comparative study - Ventura, Walter (2009)
Introduction: There are reports from several countries on good outcomes with Misgav Ladach’s cesarean section technique use. Objetives: To determine results obtained with Misgav Ladach’s cesarean technique and to compare them with the traditional Kerr’s cesarean section. Design: Retrospective, comparative study. Setting: Hospital II, EsSalud, Huamanga, Ayacucho. Participants: Full term pregnant women with a single fetus and medical indication for cesarean section. Interventions: Cesarean section. Main outcome measures: Surgical time, time to fetal birth, blood loss, use of post operative analgesia. Results: Mean surgical time was 25 and 38 minutes with respectively Misgav Ladach’s and Kerr’s techniques. Time to fetal birth was 79 seconds in cases vs. 139 seconds in the control group with significant difference. Mean hemoglobin was 1,2 g/dL significantly less in cases than 1,47 in the control group. Furthermore, the cases group needed less analgesia than the control group. Fever and need of antibiotics following surgery did not show significant differences. Conclusions: Misgav Ladach’s cesarean section seems to be more beneficial than traditional cesarean section, to be confirmed in future studies.